Evidence based decision of the Philippines to join regional seed cooperation. - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
CIP organized a Policy Forum in Manila on 7 February 2019 to discuss the importance of `Siem Reap POD?. This was followed by the visit of a high-level delegation to South Asia and webinars (in collaboration with PCCAARD) on the seed systems and the regional seed cooperation. The webinars participants expressed strong support for the Philippines joining the regional seed cooperation. CIP circulated a position paper on the benefits of the Philippines joining the regional cooperation in seed sector.